George Alfred Trenholm papers - Trenholm, George Alfred, 1806-1876.
Volumes containing personal and official correspondence, Confederate Treasury records and archives, notes, bills, bonds, and a seal of the Confederate Treasury. Correspondents include Jefferson Davis, Duncan F. Kenner, Jean Laffite, and William H. Seward.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
Confederate secretary of the treasury, cotton merchant, and South Carolina legislator.
Collection material in English.
Keywords: Davis, Jefferson, -- 1808-1889 -- Correspondence; Kenner, Duncan Farrar, -- 1813-1887 -- Correspondence; Laffite, Jean -- Correspondence; Seward, William Henry, -- 1801-1872 -- Correspondence; Confederate States of America. -- Department of the Treasury; Finance, Public -- Confederate States of America; Cabinet officers -- Confederate State of America; Legislators -- South Carolina; Merchants